PENGARUH MOTIVASI BELAJAR DALAM MENGHADAPI ASESMEN STANDARISASI PENDIDIKAN DAERAH (ASPD) - Irfan Rahmawanto; Henry Aditia Rigianti (STKIP Subang, 2023)
This study aims to determine the effect of learning motivation in dealing with regional education standardization assessments. This research uses interview methods and literature study. The researcher made observations at Sidomulyo State Elementary School on Tuesday 27 June 2023. The researcher also used the interview method with the resource person, a class VI teacher, Mrs. Nuri Mustikasari, S.Pd SD. The researcher uses the literature study method by finding sources of knowledge from several previous studies through journals related to the research to be studied. The results of the study showed that SD Negeri Sidomulyo had carried out a Standardized Assessment of Regional Assessments to increase students' learning motivation, especially grade VI students.